2012
DOI: 10.1371/journal.pone.0040715
|View full text |Cite
|
Sign up to set email alerts
|

Plum (Prunus domestica) Trees Transformed with Poplar FT1 Result in Altered Architecture, Dormancy Requirement, and Continuous Flowering

Abstract: The Flowering Locus T1 (FT1) gene from Populus trichocarpa under the control of the 35S promoter was transformed into European plum (Prunus domestica L). Transgenic plants expressing higher levels of FT flowered and produced fruits in the greenhouse within 1 to 10 months. FT plums did not enter dormancy after cold or short day treatments yet field planted FT plums remained winter hardy down to at least −10°C. The plants also displayed pleiotropic phenotypes atypical for plum including shrub-type growth habit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 23 publications
7
94
0
1
Order By: Relevance
“…Transgenic apple plants that express 35S::MdFT1 show early flowering and promotion of flower development within a year after transformation (Kotoda et al 2010;Tränkner et al 2010). Similarly strong promotion of flowering by FT overexpression has been reported for the woody plants poplar, citrus, pear and plum (Endo et al 2005;Hsu et al 2006;Matsuda et al 2009;Srinivasan et al 2012). These results indicate that FT genes from woody plants are highly conserved as a floral activator.…”
supporting
confidence: 65%
“…Transgenic apple plants that express 35S::MdFT1 show early flowering and promotion of flower development within a year after transformation (Kotoda et al 2010;Tränkner et al 2010). Similarly strong promotion of flowering by FT overexpression has been reported for the woody plants poplar, citrus, pear and plum (Endo et al 2005;Hsu et al 2006;Matsuda et al 2009;Srinivasan et al 2012). These results indicate that FT genes from woody plants are highly conserved as a floral activator.…”
supporting
confidence: 65%
“…Genetic transformation in European plum (Prunus domestica L.) has been established through regeneration of the cotyledon and hypocotyl sections of mature embryos (Mante et al, 1989;Scorza et al, 1994), immature embryos and embryonic axes (Tian et al, 2007a;Srinivasan et al, 2012;Petri et al, 2012: Wang et al, 2013. Medium supplemented with thidiazuron (TDZ) 7.5 μM in combination with indole-3-butyric acid (IBA) 0.25 μM has been used for shoot regeneration, with a transformation effi ciency of 1.2% (Scorza et al, 1994;González-Padilla et al, 2003).…”
Section: Genetic Transformationmentioning
confidence: 99%
“…Petri et al (2012) reported 42% transformation effi ciency increase using 9 μM 2,4-dichlorophenoxyacetic acid (2,4-D) for three days during co-cultivation, followed by a regeneration medium containing TDZ (7.5 μM) and kanamycin 80 mg L-1 as selective agent. Using this protocol, Srinivasan et al (2012) successfully transformed European plum with the PtFT1 gene. Wang et al (2013) first reported the selection and regeneration of transgenic plants with the selection marker from E. coli.…”
Section: Genetic Transformationmentioning
confidence: 99%
“…El cultivo de ciruela HoneySweet, altamente resistente a la enfermedad de Sharka, causada por el plum pox virus (PPV) (Scorza et al, 2013) se cruzó con plántulas de ciruela pasa tipo California, con el fin de segregar en estas últimas el gen de resistencia. Para acelerar las cruzas sexuales se sobre expresó el gen FT1 de Populus trichocarpa (PtFT) en plántulas de ciruela (Srinivasan et al, 2012); se obtuvo floración en menos de un año. Las plántulas obtenidas de estas cruzas se analizaron por medio de marcadores moleculares para el transgen de resistencia a PPV y el gen de inducción de floración FT, las positivas se cruzaron con ciruela pasa tipo-California para segregar la resistencia a PPV de HoneySweet.…”
Section: Mejoramiento Biotecnológico Acelerado De áRbolesunclassified